A high-performance vitrified microsphere thermal insulation mortar and its preparation method and use

By adding specific additives to the vitrified microbead insulation mortar, its crack resistance, insulation and flame retardant properties are improved, and the problems of poor insulation effect, large water absorption and easy cracking in the prior art are solved, and it is suitable for various climates High-performance insulation mortar under conditions.

CN116789417BInactive Publication Date: 2025-02-14LANZHOU UNIVERSITY OF TECHNOLOGY +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310788752.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the use of existing vitrified microbead insulation mortar, there are problems such as poor insulation effect, large water absorption rate and easy cracking, especially in severe cold, cold and cold climates in summer and cold winter, resulting in degradation of insulation performance and material aging.

Method used

By adding microcapsule phase-change paraffin, basalt fiber, zinc borate, high-concentrated silicone and dispersible latex powder to the vitrified microbead insulation mortar, the crack resistance, insulation and flame retardant properties of the mortar are improved.

Benefits of technology

It has achieved the development of high-performance vitrified microbead insulation mortar, with excellent insulation, flame retardant, water repellent and crack resistance, and is suitable for exterior wall insulation projects of residential buildings in severe cold, cold and cold areas in summer and cold winter.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a high-performance glass microsphere thermal insulation mortar and its preparation method and use, wherein the thermal insulation mortar includes microcapsule phase change paraffin as a thermal insulation component, a highly concentrated silicone hydrophobic agent as a waterproof component, a zinc borate flame retardant as a flame retardant component, and basalt fiber as an anti-cracking component. The high-performance glass microsphere thermal insulation mortar obtained by the present invention has a linear shrinkage of less than or equal to 0.297%, a thermal conductivity of less than or equal to 0.0458W / (mK), and a continuous burning time of less than or equal to 23.85s. The thermal insulation mortar of the present invention can meet the requirements of flame retardancy, thermal insulation, hydrophobicity, and crack resistance of thermal insulation materials for the exterior walls of residential buildings under severe cold, cold, and hot summer and cold winter climate conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of inorganic materials, and in particular to a high-performance vitrified microsphere thermal insulation mortar and a preparation method and application thereof. Background Art

[0002] Improving the thermal insulation performance of the wall is helpful for energy conservation. The thermal insulation of the exterior walls of residential buildings is often achieved by adding inorganic thermal insulation materials or organic thermal insulation materials to the walls. Organic thermal insulation materials are not resistant to aging, have poor stability, large deformation coefficient, and are easy to burn. Therefore, it is necessary to vigorously develop inorganic thermal insulation materials that are flame retardant, durable, and can actively reduce building energy consumption. Rock wool board and vitrified microsphere insulation mortar are currently commonly used inorganic thermal insulation materials; among them: rock wool board has the advantages of good thermal insulation effect, strong fire resistance, and good economy. However, rock wool board also has the disadvantages of cumbersome construction process, not synchronized with the life of the building structure, and cannot be used for special-shaped structures; vitrified microsphere insulation mortar has the advantages of good construction performance and a wide range of applications, and has received widespread attention in residential building exterior wall thermal insulation projects.

[0003] However, during the use of the vitrified micro-bead insulation mortar in the prior art, if it is subjected to long-term soaking in water vapor or water, the thermal insulation performance of the mortar will be greatly reduced. In particular, after absorbing water, the mortar will become loose and bulge and crack under the action of freezing, which will eventually lead to the weakening of the mortar strength and accelerate the aging of the insulation material. On the other hand, the thermal conductivity of the existing vitrified micro-bead insulation mortar is relatively high, and it cannot achieve the energy-saving effect of the residential building exterior wall insulation system in severe cold and cold areas, resulting in poor insulation effect. Finally, the shrinkage rate of the existing vitrified micro-bead insulation mortar is large, and it is easy to crack during the mortar hardening process. In particular, after water enters the cracks, the thermal insulation performance of the mortar is greatly reduced and bulges. In more serious cases, peeling occurs between the insulation mortar layer and the exterior wall interface layer, which causes great damage to the thermal insulation performance and durability of the exterior wall of the residential building.

[0004] Therefore, the existing vitrified microsphere insulation mortar generally faces problems such as poor insulation effect, high water absorption, and easy cracking during use, which greatly limits the application of vitrified microsphere insulation mortar in residential building exterior wall insulation projects. In order to improve the insulation performance, water resistance and crack resistance of the existing vitrified microsphere insulation mortar, a high-performance vitrified microsphere insulation mortar suitable for various meteorological conditions is developed, which is of great significance for residential building exterior wall insulation projects in severe cold, cold and hot summer and cold winter areas. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and to propose a high-performance vitrified microsphere thermal insulation mortar and its preparation method and use. The above-mentioned thermal insulation mortar is suitable for extremely cold, cold and hot-summer-cold-winter areas, and has high thermal insulation, flame retardant, hydrophobic and crack-resistant properties.

[0006] The invention discloses a high-performance vitrified microsphere thermal insulation mortar, wherein the linear shrinkage of the thermal insulation mortar is less than or equal to 0.297%, the thermal conductivity is less than or equal to 0.0498 W / (mK), and the continuous burning time is less than or equal to 23.85 s.

[0007] Furthermore, the thermal insulation mortar of the present invention comprises vitrified microspheres, microcapsule phase-change paraffin, basalt fiber, zinc borate, highly concentrated organic silicon and dispersible latex powder.

[0008] The vitrified microspheres are hollow spherical ultra-light inorganic non-metallic materials. The vitrified microspheres have a specific gravity of less than 0.1, a particle size of 0.08-0.1 mm, a cylinder pressure strength of more than 142 kPa, a thermal conductivity of less than 0.031 W / (mK), and a volume water absorption rate of less than 23.1%.

[0009] In the present invention, microcapsule phase-change paraffin is used to improve thermal insulation performance, highly concentrated silicone hydrophobic agent is used as hydrophobic component, zinc borate is used as flame retardant component, and basalt fiber is used as anti-cracking component. By adding microcapsule phase-change paraffin, highly concentrated silicone hydrophobic agent, zinc borate, and basalt fiber to the vitrified microsphere thermal insulation mortar, the anti-cracking performance of the vitrified microsphere thermal insulation mortar is significantly improved; thus, the obtained high-performance vitrified microsphere thermal insulation mortar has thermal insulation, flame retardant, hydrophobic and anti-cracking properties, and at the same time solves the problem of bulging and cracking caused by frost heave of the vitrified microsphere thermal insulation mortar in a severe cold and humid environment.

[0010] The present invention adopts microcapsule phase change paraffin to replace part of the vitrified microspheres, and the obtained vitrified microsphere insulation mortar has excellent thermal insulation performance. This is because the microcapsule phase change paraffin is a typical phase change material, which has the ability to change its physical state within a certain temperature range. When the temperature rises to the melting point, the microcapsule phase change paraffin absorbs and stores a large amount of latent heat. When cooled, the heat stored in the microcapsule phase change paraffin is dissipated into the environment. During the phase change process, the microcapsule phase change paraffin uses the special property of storing or releasing heat to improve the thermal insulation performance of the thermal insulation mortar.

[0011] The highly concentrated organic silicon water repellent in the present invention reacts with carbon dioxide in the air to form a silicone resin waterproof film with waterproof performance, thereby solving the problem of reduced thermal insulation performance and swelling caused by water absorption of thermal insulation mortar.

[0012] The zinc borate flame retardant in the present invention has the function of absorbing heat and diluting combustibles. When the temperature is higher than 300°C, the zinc borate undergoes thermal decomposition to release crystal water, which plays the role of absorbing heat, cooling and diluting oxygen in the air, thereby preventing the mortar from catching fire and improving the fire resistance of the thermal insulation mortar.

[0013] The basalt fiber in the present invention has a significant cross-linking effect, forms a three-dimensional structure in the vitrified microsphere thermal insulation mortar, and improves the anti-cracking performance of the vitrified microsphere thermal insulation mortar.

[0014] The cement described in the present invention can be P.O42.5 ordinary Portland cement.

[0015] Furthermore, in the dry powder component of the thermal insulation mortar of the present invention, the mass fraction of the vitrified microspheres is a, the mass fraction of the microcapsule phase change paraffin is b, the mass fraction of the cement is c, and a, b and c satisfy the relationship:

[0016] b = 2850e -27.4a , c = 6a 2 -5a+k, (k is a constant term)

[0017] And 40%≤a<45%, 1.56≤k<1.70, 97%<a+b+c<100%;

[0018] The mass fraction of the cellulose ether is ɑ, the mass fraction of the zinc borate is β, the mass fraction of the basalt fiber is γ, and the mass fraction of the dispersible latex powder is ε;

[0019] Among them, ɑ, β, γ and ε satisfy the relationship: ɑ + β + γ + ε≤1.97%, and ɑ>0, 0<β≤0.5%, γ>0, ε>0;

[0020] The balance is the highly concentrated organic silicon, the mass fraction of the highly concentrated organic silicon is δ, and δ>0.

[0021] Furthermore, the microcapsule phase-change paraffin wax in the thermal insulation mortar of the present invention has a smooth and rounded surface, a particle size distribution of 10-35 μm, a phase-change melting point of 28±2.5° C., and a phase-change enthalpy value of ≥185 J / G.

[0022] Furthermore, the microcapsule phase-change paraffin wax in the thermal insulation mortar of the present invention is a phase-change material prepared by an in-situ polymerization method, and the microcapsule phase-change paraffin wax has paraffin as a core material and melamine resin as a capsule wall.

[0023] Furthermore, in the dry powder component of the thermal insulation mortar in the thermal insulation mortar of the present invention, 0.23% ≤ ɑ ≤0.28%, 0.55% ≤ γ ≤ 0.68%, 0.48% ≤ ε ≤ 0.52%, and 0.9% ≤ δ ≤ 1%.

[0024] Furthermore, the basalt fiber in the thermal insulation mortar of the present invention is a continuous fiber with a length of 5 mm and a diameter of 16 μm, which is obtained by melting basalt material at 1450° C. to 1500° C. and then drawing it at high speed through a platinum-rhodium alloy drawing plate.

[0025] Furthermore, the dispersible latex powder in the thermal insulation mortar of the present invention is a copolymer of ethylene and vinyl acetate, and the cellulose ether is hydroxypropyl methyl cellulose ether.

[0026] Furthermore, the cellulose ether of the present invention is a white or off-white fibrous powder, which is used as a thickener and stabilizer for high-performance vitrified microsphere thermal insulation mortar. The zinc borate is an industrial-grade high-efficiency flame retardant with the characteristics of non-toxicity, low water solubility, high thermal stability, and good dispersibility. The dispersible latex powder is an industrial-grade water-soluble white powder. The highly concentrated silicone hydrophobic agent is a colorless, odorless, precipitation-free, floating-free, uniform waterproofing agent.

[0027] On the other hand, the present invention provides a method for preparing the thermal insulation mortar described above, comprising the following steps:

[0028] (1) Weigh the following materials according to their mass fractions: vitrified microspheres, microencapsulated phase change paraffin, cement, cellulose ether, zinc borate flame retardant, basalt fiber, highly concentrated silicone water repellent and dispersible latex powder;

[0029] (2) Pour the materials weighed in step (1) into a stirring pot and mix them. Dry-mix them at a low speed of 62±5 r / min for 25 to 30 seconds. Then add deionized water and stir at a high speed for 60 to 90 seconds to mix them evenly to obtain the thermal insulation mortar.

[0030] On the other hand, the present invention provides an application of a high-performance vitrified microsphere insulation mortar, any of which can be used to manufacture exterior walls of residential buildings in extremely cold, cold, and hot-summer-cold-winter zones.

[0031] When the thermal insulation mortar of the present invention is used on site, no special equipment is required. Drinking water can be directly added to the dry powder of the thermal insulation mortar and stirred evenly before direct construction. The mass fraction of the drinking water is 1.25 times the mass of cement.

[0032] Compared with the prior art, the present invention has the following beneficial technical effects:

[0033] (1) The present invention solves the problems of poor thermal insulation effect, high water absorption and easy cracking of existing vitrified microsphere thermal insulation mortar, so that high-performance vitrified microsphere thermal insulation mortar can be used as thermal insulation material for exterior walls of residential buildings under severe cold, cold and hot summer and cold winter climate conditions. The thermal insulation mortar described in the present invention meets the requirements of building thermal insulation mortar for exterior wall thermal insulation materials of residential buildings under various building climate zones in my country. In addition, the implementation process of the present invention is simple and is suitable for exterior wall thermal insulation projects in severe cold, cold and hot summer and cold winter zones.

[0034] (2) The high-performance vitrified microsphere thermal insulation mortar prepared by the present invention has a linear shrinkage rate of less than or equal to 0.297%, a thermal conductivity of less than or equal to 0.0498 W / (mK), and a continuous burning time of less than or equal to 23.85 seconds. It is a thermal insulation material for the exterior walls of residential buildings suitable for extremely cold, cold, and hot-summer-cold-winter zones. DETAILED DESCRIPTION

[0035] A high-performance vitrified microsphere thermal insulation mortar, the linear shrinkage of the thermal insulation mortar is less than or equal to 0.297%, the thermal conductivity is less than or equal to 0.0498W / (mK), and the continuous burning time is less than or equal to 23.85 s. The thermal insulation mortar ingredients include vitrified microspheres, microcapsule phase change paraffin, basalt fiber, zinc borate, highly concentrated silicone and dispersible latex powder. Among them, the vitrified microspheres are hollow spherical ultra-light inorganic non-metallic materials with a specific gravity of less than 0.1, a particle size of 0.08~0.1mm, a cylinder pressure strength greater than 142kPa, a thermal conductivity of less than 0.031W / (mK), and a volume water absorption rate of less than 23.1%.

[0036] In the dry powder component of the thermal insulation mortar, the mass fraction of the vitrified microspheres is a, the mass fraction of the microcapsule phase change paraffin is b, and the mass fraction of the cement is c, and a, b and c satisfy the relationship:

[0037] b = 2850e -27.4a , c = 6a 2 -5a+k, (k is a constant term)

[0038] And 40%≤a<45%, 1.56≤k<1.70, 97%<a+b+c<100%;

[0039] The mass fraction of the cellulose ether is ɑ, the mass fraction of the zinc borate is β, the mass fraction of the basalt fiber is γ, and the mass fraction of the dispersible latex powder is ε.

[0040] Among them, ɑ, β, γ and ε satisfy the relationship: ɑ + β + γ + ε≤1.97%, and ɑ>0, 0<β≤0.5%, γ>0, ε>0;

[0041] The balance is the highly concentrated organic silicon, the mass fraction of the highly concentrated organic silicon is δ, and δ>0.

[0042] The surface of the microencapsulated phase-change paraffin wax is smooth and round, with a particle size distribution of 10-35 μm, a phase-change melting point of 28±2.5°C, and a phase-change enthalpy value of ≥185 J / G.

[0043] Microcapsule phase-change paraffin is a phase-change material prepared by in-situ polymerization, with paraffin as the core material and melamine resin as the capsule wall.

[0044] Preferably, in the dry powder component of the thermal insulation mortar, 0.2% ≤ β ≤ 0.5%, 0.23% ≤ ɑ ≤ 0.28%, 0.55% ≤ γ ≤ 0.68%, 0.48% ≤ ε ≤ 0.52%, and 0.9% ≤ δ ≤ 1%.

[0045] The basalt fiber in the thermal insulation mortar is a continuous fiber with a length of 5 mm and a diameter of 16 μm, which is made by melting basalt stone at 1450°C to 1500°C and then drawing it at high speed through a platinum-rhodium alloy drawing plate.

[0046] The dispersible latex powder in the thermal insulation mortar is a copolymer of ethylene and vinyl acetate, and the cellulose ether is hydroxypropyl methyl cellulose ether.

[0047] A method for preparing the above-mentioned thermal insulation mortar comprises the following steps:

[0048] (1) Weigh the following materials according to their mass fractions: vitrified microspheres, microencapsulated phase change paraffin, cement, cellulose ether, zinc borate flame retardant, basalt fiber, highly concentrated silicone water repellent and dispersible latex powder;

[0049] (2) Pour the materials weighed in the above step (1) into a stirring pot and mix them. Dry mix them at a low speed of 62±5 r / min for 25 to 30 seconds. Then add deionized water and stir at a high speed for 60 to 90 seconds to mix them evenly to obtain the above thermal insulation mortar.

[0050] The invention discloses an application of a high-performance vitrified microsphere thermal insulation mortar, wherein the thermal insulation mortar is used for manufacturing exterior walls of residential buildings in extremely cold, cold, and hot-summer-cold-winter zones.

[0051] The present invention is further described in detail below with reference to specific embodiments and comparative examples.

[0052] Embodiment 1:

[0053] A high-performance vitrified microsphere thermal insulation mortar, the linear shrinkage of the thermal insulation mortar is less than or equal to 0.297%, the thermal conductivity is less than or equal to 0.0498W / (mK), and the continuous burning time is less than or equal to 23.85 s. The thermal insulation mortar ingredients include vitrified microspheres, microcapsule phase change paraffin, basalt fiber, zinc borate, highly concentrated silicone and dispersible latex powder. Among them, the vitrified microspheres are hollow spherical ultra-light inorganic non-metallic materials with a specific gravity of less than 0.1, a particle size of 0.08~0.1mm, a cylinder pressure strength greater than 142kPa, a thermal conductivity of less than 0.031W / (mK), and a volume water absorption rate of less than 23.1%.

[0054] In the dry powder component of the thermal insulation mortar, the mass fraction of the vitrified microspheres is a, the mass fraction of the microcapsule phase change paraffin is b, and the mass fraction of the cement is c, and a, b and c satisfy the relationship:

[0055] b = 2850e -27.4a , c = 6a 2 -5a+k, (k is a constant term)

[0056] And 40%≤a<45%, 1.56≤k<1.70, 97%<a+b+c<100%;

[0057] The mass fraction of the cellulose ether is ɑ, the mass fraction of the zinc borate is β, the mass fraction of the basalt fiber is γ, and the mass fraction of the dispersible latex powder is ε.

[0058] Among them, ɑ, β, γ and ε satisfy the relationship: ɑ + β + γ + ε≤1.97%, and ɑ>0, 0<β≤0.5%, γ>0, ε>0;

[0059] The balance is the highly concentrated organic silicon, the mass fraction of the highly concentrated organic silicon is δ, and δ>0.

[0060] The surface of the microencapsulated phase-change paraffin wax is smooth and round, with a particle size distribution of 10-35 μm, a phase-change melting point of 28±2.5°C, and a phase-change enthalpy value of ≥185 J / G.

[0061] Embodiment 2:

[0062] The only difference between Example 2 and Example 1 is that, in the dry powder component of the thermal insulation mortar, 0.23% ≤ ɑ≤ 0.28%, 0.55% ≤ γ ≤ 0.68%, 0.48% ≤ ε ≤ 0.52%, and 0.9% ≤ δ ≤ 1%.

[0063] Embodiment 3:

[0064] A high-performance vitrified microsphere thermal insulation mortar, using the following thermal insulation mortar materials in the following mass proportions:

[0065] In the dry powder component of the thermal insulation mortar, the mass fraction of the vitrified microspheres is a, the mass fraction of the microcapsule phase change paraffin is b, and the mass fraction of the cement is c, and a, b and c satisfy the relationship:

[0066] b = 2850e -27.4a , c = 6a 2 -5a+k, k=1.5614;

[0067] Vitrified microspheres: a = 40%, microencapsulated phase-change paraffin: b = 4.87%, cement: c = 52.14%.

[0068] In the dry powder components of the thermal insulation mortar, the mass fraction of cellulose ether is ɑ, the mass fraction of zinc borate is β, the mass fraction of basalt fiber is γ, the mass fraction of highly concentrated organic silicon is δ, and the mass fraction of dispersible latex powder is ε;

[0069] ɑ, β, γ and ε satisfy the relationship: ɑ + β + γ + ε = 1.91%;

[0070] Among them, cellulose ether: ɑ = 0.24%, zinc borate flame retardant: β = 0.5%, basalt fiber: γ = 0.67%, dispersible latex powder: ε = 0.5%; the balance is highly concentrated silicone water repellent: δ = 1%.

[0071] On the basis of the above materials, add 0.6518 times deionized water according to the mass multiples of the above materials.

[0072] Pour the above materials into a mixing pot, dry-mix at a low speed for 25 to 30 seconds, then add deionized water according to the above proportion, and stir at a high speed for 60 to 90 seconds to mix them evenly to obtain a vitrified microsphere insulation mortar.

[0073] The vitrified microsphere thermal insulation mortar is placed in a mold and compacted, placed in a curing box at a temperature of 20°C and a humidity of 95%, and then demoulded.

[0074] After demoulding, the specimens were placed in a standard curing box for curing for 28 days, and then the physical and mechanical properties of the mortar specimens, such as dry density, compressive strength, flexural strength, linear shrinkage, thermal conductivity, and continuous burning time, were tested.

[0075] Embodiment 4:

[0076] The only difference between Example 4 and Example 3 is that the dry powder component of the high-performance vitrified microsphere thermal insulation mortar adopts the following mass fraction ratio:

[0077] b = 2850e -27.4a , c = 6a 2 -5a+k, k=1.5633;

[0078] Vitrified microspheres: a = 40.5%, microencapsulated phase-change wax: b = 4.4%, cement: c = 52.25%;

[0079] ɑ, β, γ and ε satisfy the relationship: ɑ + β + γ + ε = 1.93%;

[0080] Among them, cellulose ether: ɑ = 0.26%, zinc borate flame retardant: β = 0.5%, basalt fiber: γ = 0.67%, dispersible latex powder: ε = 0.5%; the balance is highly concentrated silicone: δ = 1%.

[0081] On the basis of the above materials, add 0.6531 times deionized water according to the mass multiples of the above materials.

[0082] Embodiment 5:

[0083] The only difference between Example 5 and Example 3 is that the dry powder component of the high-performance vitrified microsphere thermal insulation mortar adopts the following mass fraction ratio:

[0084] b = 2850e -27.4a , c = 6a 2 -5a+k, k=1.5641;

[0085] Vitrified microspheres: a = 40.7%, microencapsulated phase change paraffin: b = 4.09%, cement: c = 52.30%.

[0086] ɑ, β, γ and ε satisfy the relationship: ɑ + β + γ + ε = 1.91%;

[0087] Among them, cellulose ether: ɑ = 0.24%, zinc borate flame retardant: β = 0.5%, basalt fiber: γ = 0.67%, dispersible latex powder: ε = 0.5%; the balance is highly concentrated silicone: δ = 1%.

[0088] On the basis of the above materials, add 0.6537 times of deionized water according to the mass multiples of the above materials.

[0089] Embodiment 6:

[0090] The only difference between Example 6 and Example 3 is that the dry powder component of the high-performance vitrified microsphere thermal insulation mortar adopts the following mass fraction ratio:

[0091] b = 2850e -27.4a , c = 6a 2 -5a+k, k=1.5645;

[0092] Vitrified microspheres: a = 40.8%, microencapsulated phase change wax: b = 3.98%, cement: c = 52.33%;

[0093] ɑ, β, γ and ε satisfy the relationship: ɑ + β + γ + δ + ε=1.89%;

[0094] Among them, cellulose ether: ɑ = 0.27%, zinc borate flame retardant: β = 0.5%, basalt fiber: γ = 0.62%, dispersible latex powder: ε = 0.5%; the balance is highly concentrated silicone: δ = 1%.

[0095] On the basis of the above materials, add 0.6541 times of deionized water according to the mass multiples of the above materials.

[0096] Embodiment 7:

[0097] The only difference between Example 7 and Example 3 is that the dry powder component of the high-performance vitrified microsphere thermal insulation mortar adopts the following mass fraction ratio:

[0098] b = 2850e -27.4a , c = 6a 2 -5a+k, k=1.5649;

[0099] Vitrified microspheres: a = 40.9%, microencapsulated phase-change paraffin: b = 3.87%, cement: c = 52.36%;

[0100] ɑ, β, γ and ε satisfy the relationship: ɑ + β + γ + ε = 1.87%;

[0101] Among them, cellulose ether: ɑ = 0.28%, zinc borate flame retardant: β = 0.5%, basalt fiber: γ = 0.59%, dispersible latex powder: ε = 0.5%; the balance is highly concentrated silicone: δ = 1%.

[0102] On the basis of the above materials, add 0.6545 times of deionized water according to the mass multiples of the above materials.

[0103] Embodiment 8:

[0104] The only difference between Example 8 and Example 3 is that the dry powder component of the high-performance vitrified microsphere thermal insulation mortar adopts the following mass fraction ratio:

[0105] b = 2850e -27.4a , c = 6a 2 -5a+k, k=1.5653;

[0106] Vitrified microspheres: a = 41.0%, microencapsulated phase-change paraffin: b = 3.77%, cement: c = 52.39%;

[0107] ɑ, β, γ and ε satisfy the relationship: ɑ + β + γ + ε = 1.91%;

[0108] Among them, cellulose ether: ɑ = 0.27%, zinc borate flame retardant: β = 0.5%, basalt fiber: γ = 0.64%, dispersible latex powder: ε = 0.5%; the balance is highly concentrated silicone: δ = 0.93%.

[0109] On the basis of the above materials, add 0.6549 times of deionized water according to the mass multiples of the above materials.

[0110] Embodiment 9:

[0111] The only difference between Example 9 and Example 3 is that the dry powder component of the high-performance vitrified microsphere thermal insulation mortar adopts the following mass fraction ratio:

[0112] b = 2850e -27.4a , c = 6a 2 -5a+k, k=1.5660;

[0113] Vitrified microspheres: a = 41.2%, microencapsulated phase change wax: b = 3.57%, cement: c = 52.45%;

[0114] ɑ, β, γ and ε satisfy the relationship: ɑ + β + γ + ε = 1.84%;

[0115] Among them, cellulose ether: ɑ = 0.28%, zinc borate flame retardant: β = 0.5%, basalt fiber: γ = 0.56%, dispersible latex powder: ε = 0.5%; the balance is highly concentrated silicone: δ = 0.9%.

[0116] On the basis of the above materials, add 0.6556 times deionized water according to the mass multiples of the above materials.

[0117] Embodiment 10:

[0118] The only difference between Example 10 and Example 3 is that the high-performance vitrified microsphere thermal insulation mortar adopts the following mass fraction ratio:

[0119] b = 2850e -27.4a , c = 6a 2 -5a+k, k=1.5673;

[0120] Vitrified microspheres: a = 41.5%, microencapsulated phase change wax: b = 3.28%, cement: c = 52.56%;

[0121] ɑ, β, γ and ε satisfy the relationship: ɑ + β + γ + ε = 1.76%;

[0122] Cellulose ether: ɑ = 0.27%, zinc borate flame retardant: β = 0.42%, basalt fiber: γ = 0.58%, dispersible latex powder: ε = 0.49%; the balance is highly concentrated silicone: δ = 0.90%.

[0123] On the basis of the above materials, add 0.657 times of deionized water according to the mass multiples of the above materials.

[0124] Comparative Example 1:

[0125] The difference between this comparative example 1 and example 3 is that the vitrified microsphere thermal insulation mortar adopts the following mass fraction ratio:

[0126] Glass microspheres: 45%, microcapsule phase change paraffin: 0%, cement: 52.65%, cellulose ether: 0.25%, zinc borate flame retardant: 0%, basalt fiber: 0.6%, dispersible latex powder: 1%, highly concentrated silicone: 0.5%.

[0127] On the basis of the above materials, add reaction water according to the mass multiple of the above materials: 0.6581 times.

[0128] Comparative Example 2:

[0129] The difference between this comparative example 2 and example 3 is that the vitrified microsphere insulation mortar adopts the following mass fraction ratio:

[0130] Glass microspheres: 41%, microencapsulated phase change paraffin: 4.2%, cement: 52.45, cellulose ether: 0.25%, zinc borate flame retardant: 0%, basalt fiber: 0.6%, dispersible latex powder: 1%, highly concentrated silicone: 0.5%.

[0131] On the basis of the above materials, add reaction water according to the mass multiple of the above materials: 0.6556 times.

[0132] The vitrified microsphere insulation mortars of the above-mentioned embodiments and comparative examples were tested for physical and mechanical properties with reference to the "Test Methods for Density, Moisture Content and Water Absorption of Inorganic Hard Insulation Products", "Test Methods for Inorganic Hard Insulation Products", "Technical Specifications for Inorganic Lightweight Aggregate Mortar Insulation Systems", "Determination of Steady-State Thermal Resistance and Related Properties of Insulation Materials - Protective Hot Plate Method", and "Test Methods for Building Material Properties". The results are shown in Table 1:

[0133] Table 1 Physical and mechanical properties of thermal insulation mortar in Examples 3 to 10 and Comparative Examples 1 and 2

[0134] Serial number <![CDATA[Dry density / (kg / m 3 )]]> Compressive strength / MPa Flexural strength / MPa Linear shrinkage / % Thermal conductivity / (W / (mK)) Continuous burning time / second Example 3 189.5 0.365 0.123 0 297 0.0378 23.85 Example 4 182.4 0.368 0.125 0.292 0.0383 21.03 Example 5 180.1 0.372 0.129 0.289 0.0394 19.23 Example 6 178.9 0.376 0.135 0.276 0.0412 17.56 Example 7 177.8 0.381 0.139 0.271 0.0427 16.75 Example 8 176.7 0.386 0.142 0.265 0.0431 15.13 Example 9 174.5 0.391 0.148 0.261 0.0448 12.25 Example 10 171.2 0.405 0.153 0.259 0.0458 9.15 Comparative Example 1 170.6 0.423 0.168 0.239 0.0561 0 Comparative Example 2 176.6 0.415 0.163 0.265 0.0406 33.52

[0135] According to Table 1, the high-performance vitrified microsphere insulation mortar prepared by the present invention for severe cold, cold and hot summer and cold winter zones has a linear shrinkage of less than or equal to 0.297%; a thermal conductivity of less than or equal to 0.0458 W / (mK); and a continuous burning time of less than or equal to 23.85 seconds. Taking Example 5 as an example, the thermal conductivity is 0.0394 W / (mK), indicating good thermal insulation performance; taking Example 5 as an example, the continuous burning time is 19.23 seconds, indicating good flame retardant performance, reaching the A-level fire protection standard for "flat building materials and products". Among them, the linear shrinkage of Example 5 meets the requirements of the "Technical Regulations for Inorganic Light Aggregate Mortar Insulation System", has good thermal insulation performance, and its flame retardant performance reaches the A-level fire protection standard. It belongs to the optimal mix ratio and can be used in residential building exterior wall insulation projects in severe cold, cold and hot summer and cold winter zones as an engineering mix ratio.

[0136] The thermal insulation mortar of the above embodiment meets the requirements of building thermal insulation mortar for residential building exterior wall thermal insulation materials under various building climate zones in my country. In addition, the thermal insulation mortar of the embodiment of the present invention has a simple implementation process and is suitable for exterior wall thermal insulation projects in severe cold, cold, and hot summer and cold winter zones. The high-performance vitrified microsphere thermal insulation mortar prepared in the above embodiment has a linear shrinkage rate of less than or equal to 0.297%, a thermal conductivity of less than or equal to 0.0498 W / (mK), and a continuous burning time of less than or equal to 23.85 seconds, and is suitable for residential building exterior wall thermal insulation materials in severe cold, cold, and hot summer and cold winter zones.

[0137] The above-mentioned specific implementation methods further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A high-performance vitrified microsphere thermal insulation mortar, characterized in that: The thermal insulation mortar has a linear shrinkage of less than or equal to 0.297%, a thermal conductivity of less than or equal to 0.0458 W / (mK), and a continuous burning time of less than or equal to 23.85 s. The dry powder of the thermal insulation mortar is composed of vitrified microspheres, microcapsule phase change paraffin, basalt fiber, zinc borate, highly concentrated silicone, cellulose ether, cement and dispersible latex powder; the vitrified microspheres are hollow spherical ultra-light inorganic non-metallic materials, the vitrified microspheres have a specific gravity of less than 0.1, a particle size of 0.08-0.1 mm, a cylinder pressure strength of more than 142 kPa, a thermal conductivity of less than 0.031 W / (mK), and a volume water absorption rate of less than 23.1%; In the dry powder component of the thermal insulation mortar, the mass fraction of the vitrified microspheres is a, the mass fraction of the microcapsule phase change paraffin is b, and the mass fraction of the cement is c, and a, b and c satisfy the relationship: b=2850e -27.4a , c = 6a 2 -5a+k, (k is a constant term) And 40%≤a<45%, 1.56≤k<1.70, 97%<a+b+c<100%; The mass fraction of the cellulose ether is ɑ, the mass fraction of the zinc borate is β, the mass fraction of the basalt fiber is γ, and the mass fraction of the dispersible latex powder is ε; Among them, ɑ, β, γ and ε satisfy the relationship: ɑ+β+γ+ε≤1.98%, and ɑ>0, 0<β≤0.5%, γ>0, ε>0; The balance is the highly concentrated organic silicon, the mass fraction of the highly concentrated organic silicon is δ, and δ>0; Among the dry powder components of the thermal insulation mortar, 0.23%≤ɑ≤0.28%, 0.55%≤γ≤0.68%, 0.48%≤ε≤0.52%, and 0.9%≤δ≤1%.

2. The thermal insulation mortar according to claim 1, characterized in that: The microcapsule phase-change paraffin wax has a smooth and round surface, a particle size distribution of 10 to 35 μm, a phase-change melting point of 28±2.5° C., and a phase-change enthalpy value of ≥185 J / G.

3. The thermal insulation mortar according to claim 2, characterized in that: The microcapsule phase-change paraffin wax is a phase-change material prepared by an in-situ polymerization method. The microcapsule phase-change paraffin wax uses paraffin wax as a core material and melamine resin as a capsule wall.

4. The thermal insulation mortar according to claim 3, characterized in that: The basalt fiber is a continuous fiber with a length of 5 mm and a diameter of 16 μm, which is formed by melting basalt material at 1450° C. to 1500° C. and then drawing it at high speed through a platinum-rhodium alloy drawing bushing.

5. The thermal insulation mortar according to claim 4, characterized in that: The dispersible latex powder is a copolymer of ethylene and vinyl acetate, and the cellulose ether is hydroxypropyl methyl cellulose ether.

6. A method for preparing the thermal insulation mortar according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) Weigh the following materials according to their mass fractions: vitrified microspheres, microencapsulated phase change paraffin, cement, cellulose ether, zinc borate flame retardant, basalt fiber, highly concentrated organosilicon water repellent and dispersible latex powder; (2) Pour the materials weighed in step (1) into a stirring pot and mix them, dry-mix them at a low speed of 62±5 r / min for 25 to 30 seconds, then add deionized water and stir at a high speed for 60 to 90 seconds to mix them evenly, thereby obtaining the thermal insulation mortar.

7. Use of a high-performance vitrified microsphere thermal insulation mortar, characterized in that: The thermal insulation mortar described in any one of claims 1 to 5 is used for manufacturing exterior walls of residential buildings in extremely cold, cold, and hot-summer-cold-winter zones.

Citation Information

Patent Citations

  • Thermal insulation building mortar and preparation process thereof

    CN101759416A

  • Fire retardant insulation mortar for building's exterior and preparation method thereof

    CN104909626A

  • Self-regulating flame-retardant polyurethane insulation material and preparation method thereof

    CN110054751A